A Load Balancing Scheme for a Server Cluster Using History Results - Abdulmohsin, Husam Ali (Iraqi Journal of Science, 2022)
Load balancing in computer networks is one of the most subjects that has got researcher's attention in the last decade. Load balancing will lead to reduce processing time and memory usage that are the most two concerns of the network companies in now days, and they are the most two factors that determine if the approach is worthy applicable or not. There are two kinds of load balancing, distributing jobs among other servers before processing starts and stays at that server to the end of the process is called static load balancing, and moving jobs during processing is called dynamic load balancing. In this research, two algorithms are designed and implemented, the History Usage (HU) algorithm that statically balances the load of a Loaded Web Server (LWS) and the Massage Passing Optimization (MPO) algorithm. HU algorithm is used at the Domain Name System (DNS) side is to minimize the time required to execute the client requests based on using history results available in one of the Web servers in the server cluster. The MPO is for optimizing the message passing between the Web servers and the DNS. This message optimization will lead to optimize the processing time in the DNS cluster required to find under-loaded Web servers that will perform the request.